Business cycle fluctuations and the distribution of consumption - Giacomo De Giorgi; Luca Gambetti (Federal Reserve Bank of New York, 2015)
This paper sheds new light on the interactions between business cycles and the consumption distribution. We use Consumer Expenditure Survey data and a factor model to characterize the cyclical dynamics of the consumption distribution. We first establish that our approach is able to closely match business cycle fluctuations of consumption from the National Account. We then study the responses of the consumption distribution to total factor productivity shocks and economic policy uncertainty shocks. Importantly, we find that the responses of the right tail of the consumption distribution, mostly comprising more highly educated individuals, to shocks that drive cyclical fluctuations are larger and quicker than in other parts of the distribution. We note that the cost of business cycle fluctuations is larger than that found using aggregate consumption and that the shocks we analyze reduce consumption inequality on impact.
Keywords: C3; D12; E21; E63; 330; consumption; inequality; cost of business cycles; heterogeneity; aggregate shocks; structural factor model; FAVAR